Design and engineering of deimmunized biotherapeutics - Griswold, Karl E; Bailey-Kellogg, Chris (Current opinion in structural biology, 2016)
[Display omitted] •Immunogenicity as a risk factor for biotherapeutic agents.•Antibody epitope deletion as a strategy to evade antidrug antibodies.•T cell epitope deletion as a strategy to silence the antidrug immune response.•Multi-objective protein design algorithms to facilitate biotherapeutic deimmunization.•Highlights of recent experimental validation for deimmunized biotherapeutics. Therapeutic proteins are powerful next-generation drugs able to effectively treat diverse and devastating diseases, but the development and use of biotherapeutics entails unique challenges and risks. In particular, protein drugs are subject to immune surveillance in the human body, and ensuing antidrug immune responses can cause a wide range of problems including altered pharmacokinetics, loss of efficacy, and even life-threating complications. Here we review recent progress in technologies for engineering deimmunized biotherapeutics, placing particular emphasis on deletion of immunogenic antibody and T cell epitopes via experimentally or computationally guided mutagenesis.